Outcomes of Non-anesthesiologist-Administered Propofol in Pediatric Gastroenterology Procedures - Lee, Frances C.; Queliza, Karen; Chumpitazi, Bruno P.; Rogers, Amber P.; Seipel, Catherine; Fishman, Douglas S. (Frontiers in Pediatrics, 2021)
Background and Aims: Non-anesthesiologist-administered propofol (NAAP) has been found to have an acceptable safety profile in adult endoscopy, but its use remains controversial and pediatric data is limited. Our aim was to examine the safety and efficacy of NAAP provided by pediatric hospitalists in pediatric endoscopy. Methods: We retrospectively reviewed 929 esophagogastroduodenoscopy (EGD), colonoscopy, and combined EGD/colonoscopy cases in children aged 5–20 years between April 2015 and December 2016 at a large children's hospital. We analyzed the data for adverse events in relation to demographics and anthropometrics, American Society of Anesthesiologists physical classification score, presence of a trainee, comorbid conditions, and procedure time. Results: A total of 929 cases were included of which 496 (53%) were completed with NAAP. Seventeen (3.4%) of NAAP cases had an adverse event including the following: 12 cases of hypoxia, 2 cardiac, and 3 gastrointestinal adverse events. General anesthesia cases had 62 (14.3%) adverse events including the following: 54 cases of hypoxia, 1 cardiac, 7 gastrointestinal, and 1 urologic adverse event. No adverse events in either group required major resuscitation. NAAP vs. general anesthesia had a lower overall adverse event rate (3.4 vs. 14.3%, p < 0.0004) and respiratory adverse event rate (2.4% vs. 12.5%, p < 0.0004). Overall, cardiac and gastrointestinal adverse event rates between the two groups were comparable. When accounting for all captured factors via logistic regression, both younger age (P < 0.001) and general anesthesia (P < 0.0001) remained risk factors for an adverse event. Conclusion: The overall adverse event rate of NAAP was low (3.4%) with none requiring major resuscitation or hospitalization. This is comparable to studies of NAAP in adult endoscopy and suggests that NAAP provided by pediatric hospitalists has an acceptable safety profile.